Streamflow Depletion Modeling: Methods for an Adaptable and Conjunctive Water Management Decision Support Tool. (25th June 2018) - Huggins, Xander; Gleeson, Tom; Eckstrand, Hailey; Kerr, Ben
Abstract: Groundwater pumping depletes streamflow, which can have significant ecological impacts depending on the magnitude of depletion relative to environmental flow needs. Streamflow depletion estimates from groundwater pumping have been quantified using both analytical and numerical methods, but are not routinely compared to environmental flow needs or used in practical water management tools. Decision support tools that incorporate groundwater dynamics are becoming increasingly necessary for water managers as groundwater regulations become more important in environmental policy, particularly concerning the preservation of environmental flow needs. We develop and apply methods for a web‐based decision support tool for conjunctive groundwater and surface water management, demonstrated using a case study watershed in British Columbia, Canada. Open‐source data are analyzed with a combination of spatial algorithms and previously developed analytical models, such that the tool can be applied to other regions. Streamflow depletion estimates are calculated in four regions in the largely undeveloped Bulkley Valley, British Columbia. Our transparent methodology has geographic and data input flexibility which is a significant improvement on currently existing water management tool methods. Abstract : Research Impact Statement : Developed a transparent, transferable methodology for quantifying how groundwater pumping depletes streamflow relative to environmental flows.